Antiviral Activity Against Infectious Bronchitis Virus and Bioactive Components of Hypericum perforatum L. - Chen, Huijie; Muhammad, Ishfaq; Zhang, Yue; Ren, Yudong; Zhang, Ruili; Huang, Xiaodan; Diao, Lei; Liu, Haixin; Li, Xunliang; Sun, Xiaoqi; Abbas, Ghulam; Li, Guangxing (Frontiers in Pharmacology, 2019)
Hypericum perforatum L., also known as Saint John’s Wort, has been well studied for its chemical composition and pharmacological activity. In this study, the antiviral activities of hypericum perforatum L. on infectious bronchitis virus (IBV) were evaluated in vitro and in vivo for the first time. The results of in vitro experiments confirmed that the antiviral component of hypericum perforatum L. was ethyl acetate extraction section (HPE), and results showed that treatment with HPE significantly reduced the relative mRNA expression and virus titer of IBV, and reduced positive green immunofluorescence signal of IBV in chicken embryo kidney (CEK) cells. HPE treatment at doses of 480-120 mg/kg for 5 days, reduced IBV induced injury in the trachea and kidney, moreover, reduced the mRNA expression level of IBV in the trachea and kidney in vivo. The mRNA expression levels of IL-6, TNF-α, and NF-κB significantly decreased, but MDA5, MAVS, IFN-α and IFN-β mRNA levels significantly increased in vitro and in vivo. Our findings demonstrated that HPE had significant anti-IBV effects in vitro and in vivo, respectively. In addition, it is possible owing to up-regulate mRNA expression of type I interferon through the MDA5 signaling pathway and down-regulate mRNA expression of IL-6 and TNF-α via the NF-κB signaling pathway. Moreover, the mainly active compositions of HPE analyzed by HPLC/ESI-MS are hyperoside, quercitrin, quercetin, pseudohypericin and hypericin, and a combination of these compounds could mediate the antiviral activities. This might accelerate our understanding of the antiviral effect of hypericum perforatum L. and provide new insights into the development of effective therapeutic strategies.